Radiation-Induced Graft Copolymerization of Monomer Mixture onto Sugarcane Bagasse for Removal of Cu(II) Ions: A Comparative Study - S. Rajurkar, Nilima; Dimya, Kumaree; N. Gokarn, Ashok (Asian Journal of Chemistry, 2012)
Removal of copper(II) ions from aqueous solution was carried out using acid treated sugarcane bagasse (ATSB), irradiated sugarcane bagasse (ISB), irradiated acid treated sugarcane bagasse (IATSB) and radiation induced graft copolymerized sugarcane bagasse (RIGCSB). For this purpose sugarcane bagasse was irradiated in Co-60 g-chamber 900A with a dose rate of 3.7 Gy/ min. The radiation induced graft polymerization was carried out using CH3CN/DMF at a dose of 6 kGy. Copper(II) ions were removed by batch adsorption process at determined optimized parameters viz. pH 3, dosage 2 g of 250 μm of adsorbent and contact time 120 min. The percentage removal of the modified adsorbent was found to be significant and in the order RIGCSB (82.9 %) > ATSB (72 %)> IATSB (81.9 %), while ISB did not adsorb Cu(II) ions. Thus, the modified adsorbents proved to be promising material for removal of Cu(II) ions.